2009
DOI: 10.1111/j.1365-2133.2009.09308.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct patterns of brain activity evoked by histamine-induced itch reveal an association with itch intensity and disease severity in atopic dermatitis

Abstract: Summary Background Little is known about brain mechanisms supporting the experience of chronic puritus in disease states. Objectives To examine the difference in brain processing of histamine-induced itch in patients with active atopic dermatitis (AD) vs. healthy controls with the emerging technique of functional magnetic resonance imaging (fMRI) using arterial spin labelling (ASL). Methods Itch was induced with histamine iontophoresis in eight patients with AD and seven healthy subjects. Results We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
150
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(167 citation statements)
references
References 65 publications
13
150
3
1
Order By: Relevance
“…This shared network includes the anterior insula, premotor cortex, primary somatosensory cortex, and prefrontal cortex. One region not activated in our study but typically activated by chemical induction of itch is the midcingulate cortex, although not all studies of itch have reported activity here (14,29). The magnitude of activation across this "itch matrix" reflects the main effect of viewing itch-related videos (relative to non-itch control stimuli), and tends to correlate with the subjective intensity of itchiness reported for these stimuli.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This shared network includes the anterior insula, premotor cortex, primary somatosensory cortex, and prefrontal cortex. One region not activated in our study but typically activated by chemical induction of itch is the midcingulate cortex, although not all studies of itch have reported activity here (14,29). The magnitude of activation across this "itch matrix" reflects the main effect of viewing itch-related videos (relative to non-itch control stimuli), and tends to correlate with the subjective intensity of itchiness reported for these stimuli.…”
Section: Discussionmentioning
confidence: 83%
“…The planning of scratching movements is linked to premotor activity, whereas the intention to scratch (or not) is linked to engagement of the prefrontal cortex (12), consistent with this area's recognized role in willed actions (13). Primary and secondary somatosensory cortices have been proposed to support the sensory (i.e., spatial, temporal, and intensity) aspects of the experience (4); however, activity within almost all parts of the itch matrix is correlated with subjective ratings of itch intensity (5,6,14), suggesting interdependence of the sensory, motor, and affective components of itch. Previous fMRI studies were constrained by the methodological limitation that the experience of histamine-induced itch emerges rather slowly, taking approximately 1 min to reach peak intensity after onset of infusion (5), followed by a slow decay.…”
mentioning
confidence: 99%
“…To date, itch has been studied using fMRI in a small number of patients with atopic dermatitis (AD), [12,[82][83][84][85][86][87] lichen simplex chronicus, [88] prurigo nodularis, [88] end-stage renal disease [89] and psoriasis. [82] Most of these studies were within-subject and placebo-controlled but without direct comparison to healthy controls.…”
Section: Itch-induced Activation Patterns Of Patients In Comparisonmentioning
confidence: 99%
“…Several studies have revealed that brain processing of itchy stimuli in patients with chronic pruritus differs from that observed in healthy controls [34][35][36]. Thus, it could be suggested that mapping of brain activity during itch episodes may provide valuable information helping in the assessment of the degree of itch intensity.…”
Section: Assessment Of Brain Activitymentioning
confidence: 99%
“…However, current data are rather preliminary, as there is great variability in currently achieved results with different diagnostic techniques. These methods are also too expensive to be used as a routine diagnostic procedure, and thus they are used only for scientific purposes to better understand what happens within the brain upon itchy stimuli [34][35][36].…”
Section: Assessment Of Brain Activitymentioning
confidence: 99%